PACk: An Efficient Partition-based Distributed Agglomerative Hierarchical Clustering Algorithm for Deduplication - Wang, Yue; Narasayya, Vivek; He, Yeye; Chaudhuri, Surajit (VLDB 2022, 2022)
The Agglomerative Hierarchical Clustering (AHC) algorithm is widely used in real-world applications. As data volumes continue to grow, efficient scale-out techniques for AHC are becoming increasingly important. In this paper, we propose a Partition-based distributed Agglomerative Hierarchical Clustering (PACk) algorithm using novel distance-based partitioning and distance-aware merging techniques. We have developed an efficient implementation of PACk on Spark. Compared to the state-of-the-art distributed AHC algorithm, PACk achieves 2× to 19× (median=9×) speedup across a variety of synthetic and real-world datasets.